/Kaggen's code: paintings of moths in southern African hunter-gatherer rock art - Hollmann, J. C. (Southern African Humanities, 2007)
This paper explores the possible meanings of uncommon hunter-gatherer rock paintings at Eland Cave in the uKhahlamba-Drakensberg Park, KwaZulu-Natal, and at Raiders 1 in Raiders Gorge, Brandburg/Daureb, Erongo Region, Omaruru District, Namibia, that have been identified as moths. The paintings are interpreted in terms of /Xam Bushman beliefs in which the appearance of a moth at the family fire heralds the killing of an animal on the hunting ground. These beliefs are part of a more general 'code' of hunting practices aimed to ensure successful kills of game animals 'owned' and protected by /Kaggen, the /Xam Bushman trickster deity. Central to this interpretation is the hypothesis that hunter-gatherer rock paintings may have been perceived as supernaturally potent images. According to this scenario the painters modelled the moth paintings on aspects of the appearance and behaviour of certain moths and positioned these on the rock face in certain ways in an attempt to create an ambience in which the balance, usually loaded in the hunted animal's favour, is in the direction of the hunters instead. To cite this article: Hollmann, J. C. 2007. /Kaggen's code: paintings of moths in southern African hunter-gatherer rock art. Southern African Humanities 19: 83-101.